Analysis of the Impact of People's Business Credit (KUR) in the Development of Micro, Small and Medium Enterprises in Telaga Jaya and Tilango Sub-Districts, Gorontalo Regency - Idham M. Ishak; Hais Dama (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to analyse the impact of People's Business Credit (KUR) in the development of Micro, Small and Medium Enterprises in Telaga Jaya District and Tilango District, Gorontalo Regency. Based on the results of the analysis, People's Business Credit (KUR) is still a prima donna for every MSME business actor. The ease provided by banks in providing KUR facilities for MSME actors is a factor that causes high interest in MSME business actors to get credit in the Telaga Jaya and Tilango sub-districts, which are mostly engaged in the culinary trade, services and agriculture business sectors. Government support for business actors to obtain KUR facilities is also a means of controlling and supervising the smooth payment of KUR by MSME business actors.